Steady-state free precession imaging of the inner ear. - Stillman, A E; Remley, K; Loes, D J; Hu, X; Latchaw, R E (American Journal of Neuroradiology, 1994)
The authors describe a steady-state free precession technique for imaging the inner ear. Although the signal-to-noise ratio is not as great as with other three-dimensional MR techniques, the inherent high contrast of inner ear structures makes this a valuable technique for patients with sensorineural hearing loss and for those who refuse paramagnetic contrast material.